Isolation and Molecular Identification of Endophytic Bacteria from Durian Arillus (Durio zibethinus Murr.) var. Matahari (Microbiology Indonesia, 2014)
Endophytes are plant-associated microorganisms that able to form colonies in internal tissue and considered as an important component of biodiversity. However, information about the existence of naturally fruits-associated endophytic bacteria at different life-history stages of hosts is very limited. Durian (Durio zibethinus Murr.) is an exotic tropical fruits with a high economical value, but the occurrence and functional role of associated endophytes remains unexplored. A total of sixteen endophytic bacterial isolates were identified by 16S rRNA sequence analysis from ripe and unripe stages of Durian fruits var. Matahari. These isolates belonged to the genus Staphylococcus, Bacillus, Enterobacter, Moraxella, Gordonia, Salmonella, Rhizobium, Brachybacterium, Kocuria, and Klebsiella. This is the first report of an endophytic bacterial spesies residing in Durian arillus. This research also indicated potency of culturable endophytes from Durian fruits in plant growth promotion.